Eksplorasi Aliran-Aliran Filsafat Pendidikan Islam: Konsep, Tokoh, dan Implikasinya dalam Pembelajaran - Subiantoro, Anjar; Mansur, Rosichin (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This study aims to describe the main concepts in the schools of Islamic educational philosophy, analyze the thoughts of the main figures in Islamic educational philosophy, and identify the influence of various schools of Islamic educational philosophy on learning in Islamic educational environments. This study uses a library study method with a descriptive-analytical approach to examine the thoughts and concepts in Islamic educational philosophy. Islamic educational philosophy is divided into three main schools, namely conservative, religious-rational, and pragmatic. The conservative school, influenced by Al-Ghazali's thoughts, emphasizes the importance of education based on the development of morals and spirituality with an orientation to the afterlife. The religious-rational school, as developed by Ikhwan al-Shafa, emphasizes the balance between religious knowledge and rational knowledge to form critical and wise individuals. Meanwhile, the pragmatic school initiated by Ibn Khaldun emphasizes the relevance of education to social and economic needs, as well as strengthening practical skills that contribute to the welfare of society. This third school provides a strong philosophical foundation in Islamic education, making it not only a means of transferring knowledge but also a vehicle for character formation and improving life skills. Thus, Islamic educational philosophy remains relevant in the modern education system as an effort to develop a more holistic, adaptive, and contextual learning model.